2010
DOI: 10.1002/eji.201040441
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microflora and interferon‐γ promote steady‐state interleukin‐7 production in vivo

Abstract: IL-7 is a major regulator of lymphocyte homeostasis; however, little is known about the mechanisms that regulate IL-7 production. To study Il7 gene regulation in vivo, we generated a novel IL-7-reporter mouse, which allows the non-invasive quantification of Il7 gene activity in live mice and, additionally, the simultaneous activation/inactivation of target genes in IL-7-producing cells. With these IL-7-reporter mice, we identify thymus, skin and intestine as major sources of IL-7 in vivo. Importantly, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 33 publications
1
102
1
Order By: Relevance
“…It has been reported that type 1 interferons and IFN-␥ are involved in IL-7 production in hepatocytes and IECs (18,26). We therefore next investigated whether C. rodentium-induced IL-7 expression in the colon was dependent on IFNs.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that type 1 interferons and IFN-␥ are involved in IL-7 production in hepatocytes and IECs (18,26). We therefore next investigated whether C. rodentium-induced IL-7 expression in the colon was dependent on IFNs.…”
Section: Resultsmentioning
confidence: 97%
“…RORgt + innate lymphoid cells and RORgt + NKT17 cells use IL-7 for their survival and expansion (19,28). Although IL-7 produced in the bone marrow, thymus, and lymph nodes clearly supports lymphocyte development and survival (29), more recent studies found that it can also be produced in nonlymphoid tissues, including intestine, skin, liver, and lung (30,31), and that it can even be induced in these sites by microbial signals (23,30,32). Because gdT-17 cells, NKT cells, and innate lymphoid cells are enriched in barrier tissues and their draining lymph nodes, we suggest that they are kept in balance, both in the steady-state and during an immune response, by competition for locally produced IL-7.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the thymus, IL-7-expressing cells were found in peripheral organs, such as abdomen, lung, skin, and intestine, where IL-17 + gd T cells were localized (50). Such peripheral and ontogenic heterogeneity of IL-7-expressing cells might explain the distribution of IL-17 + gd T cells, which receive important signals for their maintenance through IL-7Ra.…”
Section: Discussionmentioning
confidence: 99%